A Rapid Realist Review of Quality Care Process Metrics Implementation in Nursing and Midwifery Practice - Sean Paul Teeling (MDPI AG, 2021)
Quality measurement initiatives promote quality improvement in healthcare but can be challenging to implement effectively. This paper presents a Rapid Realist Review (RRR) of published literature on Quality Care-Process Metrics (QCP-M) implementation in nursing and midwifery practice. An RRR informed by RAMESES II standards was conducted as an efficient means to synthesize evidence using an expert panel. The review involved research question development, quality appraisal, data extraction, and evidence synthesis. Six program theories summarised below identify the key characteristics that promote positive outcomes in QCP-M implementation. Program Theory 1: Focuses on the evidence base and accessibility of the QCP-M and their ease of use by nurses and midwives working in busy and complex care environments. Program Theory 2: Examines the influence of external factors on QCP-M implementation. Program Theory 3: Relates to existing cultures and systems within clinical sites. Program Theory 4: Relates to nurses’ and midwives’ knowledge and beliefs. Program Theory 5: Builds on the staff theme of Programme Theory four, extending the culture of organizational learning, and highlights the meaningful engagement of nurses and midwives in the implementation process as a key characteristic of success. Program Theory 6: Relates to patient needs. The results provide nursing and midwifery policymakers and professionals with evidence-based program theory that can be translated into action-orientated strategies to help guide successful QCP-M implementation.